Navigating Scientific Progress in Radiation Oncology: Comprehensive Analysis of Clinical Trials From the Past Two Decades Using the ClinicalTrials.gov Database - Sebastian M. Christ; Maksym Fritsak; Gabriel Kobeissi; Philip Heesen; Siyer Roohani; Rifaquat Rahman; Ajay Aggarwal; Matthias Guckenberger (JCO Global Oncology)
PURPOSEOncology has experienced substantial growth in clinical trial activity over the past two decades, but a comprehensive evaluation of radiation oncology research is lacking. This study analyzed trends in radiation therapy trials using data from ClinicalTrials.gov.MATERIALS AND METHODSA comprehensive analysis was conducted on 4,253 radiation oncology trials registered in the database. Key outcomes examined included trends in trial activity over time, the geographic distribution of trials, and the phases of clinical trials conducted.RESULTSClinical trial activity in radiation oncology has increased significantly, with 4,253 trials registered by February 2024. Digestive, CNS, and head and neck cancers accounted for 49.7% of studies. Research on oligometastasis emerged in the past decade (2.2%), while hematology trials declined (9.7%). Phase II trials dominated (51.3%), with most originating in North America (58.2%). Europe (21.2%) and Asia (25.2%) have shown increasing contributions, reflecting a global shift. Only 6% of trials received industry funding, highlighting the financial challenges in the field.CONCLUSIONThese findings underscore the dynamic nature of radiation oncology research and the need to address regional disparities, advance novel technologies and drug-radiotherapy combinations through phase I and III trials, and increase industry investment.